International banking : its new dimensions - Bundesband Deutscher Banken; Bundesverband Deutscher Banken (Cologne, Germany : Bank-Verlag, 1981)
This book contains lectures delivered by prominent speakers at the 34th International Banking Summer School at Timmendorfer Strand, Germany, in August/September 1981 before an audience of more than 200 bankers from 55 countries and 4 international institutions. They cover a wide range of challenges facing international banking.
Lectures and proceedings at the 34th International Banking Summer school held at MARITIM golf-und sporthotel Timmendorfer Strand/Grmany
Includes bibliographical reference
osc 20/3/17
Loans
Keywords: Banks and banking